Evaluation of efficiency improvements and performance of coal-fired power plants with post-combustion CO2 capture - Hanak, Dawid P. (Cranfield University, 2016)
The power sector needs to be decarbonised by 2050 to meet the global target for greenhouse gas emission reduction and prevent climate change. With fossil fuels expected to play a vital role in the future energy portfolio and high efficiency penalties related to mature CO2 capture technologies, this research aimed at evaluating the efficiency improvements and alternate operating modes of the coal-fired power plants (CFPP) retrofitted with post-combustion CO2 capture. To meet this aim, process models of the CFPPs, chilled ammonia process (CAP) and calcium looping (CaL) were developed in Aspen Plus® and benchmarked against data available in the literature. Also, the process model of chemical solvent scrubbing using monoethanolamine (MEA) was adapted from previous studies. Base-load analysis of the 580 MWel CFPP retrofits revealed that if novel CAP retrofit configurations were employed, in which a new auxiliary steam turbine was coupled with the boiler feedwater pump for extracted steam pressure control, the net efficiency penalty was 8.7–8.8% points. This was close to the 9.5% points in the MEA retrofit scenario. Conversely, CaL retrofit resulted in a net efficiency penalty of 6.7–7.9% points, depending on the fuel used in the calciner. Importantly, when the optimised supercritical CO2 cycle was used instead of the steam cycle for heat recovery, this figure was reduced to 5.8% points. Considering part-load operation of the 660 MWel CFPP and uncertainty in the process model inputs, the most probable net efficiency penalties of the CaL and MEA retrofits were 9.5% and 11.5% points, respectively. Importantly, in the CaL retrofit scenarios, the net power output was found to be around 40% higher than that of the CFPP without CO2 capture and double than that for the MEA retrofit scenario. Such performance of the CaL retrofit scenario led to higher profit than that of the 660 MWel CFPP without CO2 capture, especially if its inherent energy storage capability was utilised. Hence, this study revealed that CaL has the potential to significantly reduce the efficiency and economic penalties associated with mature CO2 capture technologies.
Keywords: Energy storage; probabilistic performance analysis; CO2 capture technologies; efficiency improvement; process modelling; simulation